Simulation of structural response under high frequency ground excitation. - Lu, Yong (Earthquake engineering & structural dynamics.)
The structural response to high frequency ground motions is complicated due to the involvement of local mode vibration. At present such a characteristic is not well recognized and this can cause confusion over the analytical and experimental modelling of the corresponding response and damage. The fact that most existing regulatory guides for limits on allowable construction vibrations are necessarily simplified for administrative reasons calls upon the derivation of more sophisticated approaches for special cases. This requires accumulation of pertinent experimental evidence. This paper attempts to provide some insights into the local mode dynamic response characteristics, with emphasis on appropriate modelling techniques and experimental measurements. A preliminary testing program is reported, in which efforts were made to reproduce high frequency response with a reduced scale reinforced concrete model with shaking table facilities. The results demonstrate the dependence of the response amplitudes with the excitation frequency. On a ppv basis, the current test results indicate that a substantial increase of the allowable ppv value from those specified by various standards may be considered for structural damaage to reinforced concrete building structures. More analytical and experimental data are needed for further evaluation of the local mode effects and to quantify their impact on the structural damage process.